Eye gaze modeling using Tobii eye tracker for anxiety and mental health detection on Politeknik Negeri Jember student: A case study - Agustianto, Khafidurrohman; Suryani, Arinda Lironika; Kustiari, Tanti; Kamal, Mushthofa (P3M Politeknik Negeri Jember, 2025)
Education development is one of United Nation (UN) sustainable development goals (SDGs) number 4 program, where Indonesian ministry of education designed new education curriculum in 2019. Merdeka Belajar program is comprised of certified internship and independent study, which often became a graduation requirement especially for engineering major. However, rapid change in curriculum frequently caused disruption on student concentration that leads into decline in learning motivation and raising anxiety symptom. This research aims to monitor engineering students’ anxiety during courses. Anxiety-ridden students perform poorly on assignments and have a mediocre interest in studying. The eye gaze can be linked with stress level. Its pattern reflects the anxious state that befalls engineering students. Our paper's primary contribution is offering an observational result on how to use eye gazing to address the anxiety that engineering students experience by observing students' eye movements. The 16 zones (1a, 1b, 1c, 1d, 2a, 2b, 2c, 2d, 3a, 3b, 3c, 3d, 4a, 4b, 4c, 4d) make up the eye gazing pattern. 53.8% of the student experience moderate anxiety, while 26.1% of respondent suffers severe anxiety. The research's accuracy rate is 85.5%. These findings offer recommendations for how teachers might quickly assess students' anxiety levels and take specific action to support students in achieving their best learning outcomes.